Intermediate Accounting - Kieso, Donald E.; Weygandt, Jerry J.; Warfield, Terry D. (New York : Wiley, 2014)
this edition of "intermediate...." represents an important milestone in the evolution of this textbook .
(3SjO GdJhfSj (B/ (3cJH cdjI GdGbJUGO hGdGOGQI(B.s
IFRS EDITION.
Includes bibliographical references and index.
All Ages.
Keywords: Accounting